Determination of the minimal essential nucleotide sequence for diphtheria tox repressor binding by in vitro affinity selection. - Tao, X (1994)
The expression of diphtheria toxin in lysogenic toxigenic strains of Corynebacterium diphtheriae is controlled by the heavy metal ion-activated regulatory protein DtxR. In the presence of divalent heavy metal ions, DtxR specifically binds to the diphtheria tox operator and protects a 27-bp interrupted palindromic sequence from DNase I digestion. To determine the consensus DNA sequence for DtxR binding, we have used gel electrophoresis mobility-shift assay and polymerase chain reaction (PCR) amplification for in vitro affinity selection of DNA binding sequences from a universe of 6.9 x 10(10) variants. After 10 rounds of in vitro affinity selection, each round coupled with 30 cycles of PCR amplification, we isolated and characterized a family of DNA sequences that function as DtxR-responsive genetic elements both in vitro and in vivo. Moreover, these DNA sequences were found to bind activated DtxR with an affinity similar to that of the wild-type tox operator. The DNA sequence analysis of 21 unique in vitro affinity-selected binding sites has revealed the minimal essential nucleotide sequence for DtxR binding to be a 9-bp palindrome separated by a single base pair.